2018
DOI: 10.2337/db17-1336
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Soluble Epoxide Hydrolase 2 Ameliorates Diabetic Keratopathy and Impaired Wound Healing in Mouse Corneas

Abstract: EPHX2 (encoding soluble epoxide hydrolase [sEH]) converts biologically active epoxyeicosatrienoic acids (EETs), anti-inflammatory and profibrinolytic effectors, into the less biologically active metabolites, dihydroxyeicostrienoic acids. We sought to characterize the expression and the function of EPHX2 in diabetic corneas and during wound healing. The expression of EPHX2 at both mRNA and protein levels, as well as sEH enzymatic activity, was markedly upregulated in the tissues/cells, including corneal epithel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 49 publications
0
22
0
Order By: Relevance
“…While a complete understanding of the role that sEH plays in glucose homeostasis has yet to emerge, sEH ablation increases pancreatic islet size and insulin signaling in high fat fed mice (Luria et al, 2011). Conversely, overexpression of this enzyme is associated with diabetes‐associated comorbidities including diabetic retinopathy and impaired wound healing (Hu et al, 2017; Sun et al, 2018). Despite the possibility that changes in sEH activity play a role in pre‐ versus post‐intervention OxL differences in our cohort, the sEH product/precursor ratios (diols:epoxides) for 9,10‐DiHODE, 12,13‐DiHODE, and 9,10‐DiHOME were not convincingly altered (~4%, 12%, 11% reductions, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…While a complete understanding of the role that sEH plays in glucose homeostasis has yet to emerge, sEH ablation increases pancreatic islet size and insulin signaling in high fat fed mice (Luria et al, 2011). Conversely, overexpression of this enzyme is associated with diabetes‐associated comorbidities including diabetic retinopathy and impaired wound healing (Hu et al, 2017; Sun et al, 2018). Despite the possibility that changes in sEH activity play a role in pre‐ versus post‐intervention OxL differences in our cohort, the sEH product/precursor ratios (diols:epoxides) for 9,10‐DiHODE, 12,13‐DiHODE, and 9,10‐DiHOME were not convincingly altered (~4%, 12%, 11% reductions, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating studies have reported that the alteration in the JAK/STAT pathway may result in impaired wound healing in a diabetes model and promotes alternative activation of macrophage [3944]. Activated STAT3 induces the upregulation of iNOS expression, increases NO production in keratinocytes, and promotes angiogenesis in the wound tissue [45].…”
Section: Discussionmentioning
confidence: 99%
“…The loss of sEH also restored wound-induced STAT3 signaling and heme oxygenase-1 (HO-1) expression that were downregulated by hyperglycemic conditions. Similarly, sEH inhibition with subconjunctival 10 nM t -AUCB or clinical candidate inhibitor GSK2256294A (Table 1) promoted epithelial wound healing and restored HO-1 expression in diabetic mouse corneas (Sun et al, 2018).…”
Section: Diabetic Keratopathymentioning
confidence: 98%
“…Diabetic keratopathy is characterized by delayed corneal epithelial wound healing and epithelial erosion, resulting in a compromised defense system against corneal injury and infective agents (Kaji, 2005). sEH is a potential therapeutic target for diabetic keratopathy, as tested in a mouse model where corneal erosions develop upon a single corneal debridement wound (Sun et al, 2018). The expression and enzymatic activity of sEH were increased in the corneal epithelial cells of streptozotocin-induced diabetic epithelial unwounded and wounded mice compared to control mice.…”
Section: Diabetic Keratopathymentioning
confidence: 99%